Proteomic analysis of young sugarcane plants with contrasting salt tolerance - Chiconato, Denise A. [UNESP]; Santana Costa, Marilia G. de [UNESP]; Balbuena, Tiago S. [UNESP]; Munns, Rana; Santos, Durvalina M. M. dos [UNESP] (Csiro Publishing, 2021)
Soil salinity affects sugarcane (Saccharum officinale L.) production in arid and semiarid climates, severely reducing productivity. This study aimed to identify differentially regulated proteins in two cultivars that differ markedly in tolerance of saline soil. Plants were grown for 30 days and then subjected to treatments of 0 and 160 mM NaCl for 15 days. The tolerant cultivar showed a 3-fold upregulation of lipid metabolising enzymes, GDSL-motif lipases, which are associated with defence to abiotic stress, and which were not upregulated in the sensitive cultivar. Lipoxygenase was 2-fold upregulated in the tolerant cultivar but not in the sensitive cultivar, as were Type III chlorophyll a/b binding proteins. Other differences were that in the sensitive cultivar, the key enzyme of C-4 photosynthesis, phosphoenolpyruvate carboxylase was downregulated, along with other chloroplast enzymes. Na+ concentrations had not reached toxic concentrations in either cultivar by this time of exposure to salt, so these changes would be in response to the osmotic effect of the soil salinity, and likely be in common with plants undergoing drought stress.
Keywords: Saccharum; acylhydrolase; peroxiredoxin; sodium exclusion; sugarcane; salinity